2022
DOI: 10.3390/ani12121527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microalgae Addition and Fish Feed Supplementation in the Integrated Rearing of Pacific White Shrimp and Nile Tilapia Using Biofloc Technology

Abstract: This study aims to evaluate a Pacific white shrimp and Nile tilapia integrated system using biofloc technology with or without the addition of the microalgae Scenedesmus obliquus and with or without fish feed supplementation in a two-factor 62-day experiment. The shrimp (2.16 ± 0.01 g) were reared under a density of 400 shrimp m−3 and the fish (1.53 ± 0.12 g) were reared under a density of 522 fish m−3. The microalgae was added to the culture water two times a week. Growth performance, sludge production, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Therefore, a gradual enrichment in nutrients is an important factor that constrains bacterial communities in shrimp-rearing waters. This phenomenon aligns with our prior research findings [9,10,17]. Moreover, the water discharged from a shrimp-rearing system can undergo treatment through external aquaculture wastewater treatment systems [39].…”
Section: The Unequal Effects Of Microalgae and Nutrient Factors On Ba...supporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, a gradual enrichment in nutrients is an important factor that constrains bacterial communities in shrimp-rearing waters. This phenomenon aligns with our prior research findings [9,10,17]. Moreover, the water discharged from a shrimp-rearing system can undergo treatment through external aquaculture wastewater treatment systems [39].…”
Section: The Unequal Effects Of Microalgae and Nutrient Factors On Ba...supporting
confidence: 91%
“…Jensen [9] emphasized the significance of microalgae, specifically Thalassiosira fluviatilis, in enhancing the weight gain and survival of Farfantepenaeus paulensis shrimp in nursery tanks. Additionally, the introduction of microalgae, particularly Scenedesmus obliquus, improved fish survival in an integrated shrimp and fish culture system using biofloc technology [10]. These findings strongly suggest that microalgae inoculation can significantly enhance the performance and sustainability of shrimp-rearing systems.…”
Section: Introductionmentioning
confidence: 82%
“…Microbes can produce carbohydrates, lipids, proteins, minerals, and vitamins (Wang et al, 2021 ; Akkaya and Can-Guven, 2022 ; Kurniawan et al, 2022 ). Proteins are essential in human diets and animal feed formulations (Silva et al, 2022 ; Pyne et al, 2022 ). Aspergillus, Corynebacterium , and Brevibacterium are examples of amino acid sources used in dietary and feed supplements (Aizat et al, 2019 ; Karimi et al, 2021 ).…”
Section: Foods and Nutrient Sources For Humans And Livestockmentioning
confidence: 99%
“…Research has been conducted to increase the growth and production of proteins, fatty acids, and carotenoids from Chlorella, Spirulina, Aphanizomenon , and Chlamydomonas (Bleakley et al, 2017 ; Caporgno et al, 2018 ; Wang et al, 2021 ; Acquah et al, 2021 ; Pyne et al, 2022 ). Scenedesmus and Chlorella are used in bio-floc systems and fish feed supplements to enhance the growth of Pacific white shrimp and Nile tilapia (Silva et al, 2022 ).…”
Section: Foods and Nutrient Sources For Humans And Livestockmentioning
confidence: 99%
“…On the other hand, studies that consider the role of microeukaryotes in the system have revealed that the stability of a biofloc system with zero or minimal water exchange depends on the dynamic interaction between bacteria, fungi, protozoans, nematodes and rotifers, where phytoplankton and heterotrophic and nitrifying bacteria have the most crucial role in N and C utilisation (Emerenciano et al, 2017). In addition, microalgae are relevant for N and P absorption and provide greater nutritional value to the bioflocs, especially in integrated intensive aquaculture systems (Silva et al, 2022).…”
Section: The Holobiome Of the Aquaculture System And Eco-efficiencymentioning
confidence: 99%